Bridge Failures in Nepal: Systematic Review and Quantitative Characterization of Causal Mechanisms - K.C., Ravin; Dahal, Alok; Bade, Rupshikha; Khatiwada, Rajiv; Jha, Pratyush; Kafle, Shesh Raj; Marasini, Aabiskar (International Journal on Engineering Technology and Infrastructure Development, 2026)
This comprehensive systematic review of 56 reported incidents synthesizes quantitative analysis of motorable bridge failures in Nepal over the past two decades. The study gathers failure data from news archives, academic literature, and grey reports, sorting causes into hydraulic/hydrological events, construction errors, design and structural flaws, overloading, and other miscellaneous factors. The findings reveal that hydraulic failures, which are primarily linked to floods and scour, dominated by 39.29% of cases, followed by construction failures at 28.57%. The remaining causes comprise design flaws, overloading, and external events. The results underscore the structural flaw in engineering and construction methods, and the serious difficulties posed by Nepal’s dynamic river systems, monsoonal intensity, and seismicity. In order to enhance the resilience of Nepal’s vital transportation infrastructure, this review suggests upgrading hydrological design standards, improving quality assurance in construction, enhancing design review, and establishing a national bridge management system.